CREATING MULTIMEDIA INTERACTIVE E-LEARNING COURSES - Suvankulov Baxtiyor Mamarasulovich (Web of Journals Publishing, 2024)
This article provides the basics of creating and using an interactive electronic training course based on multimedia technologies. The article emphasizes the need to use interactive e-learning courses, how to create interactive e-learning courses and procedures in the learning process, and lecture sessions.
Keywords: multimedia, technology, interactive, e-learning, educational, multimedia technologies, information technology.